Studies on media education in university training of communicators: a scoping review - Rivadeneyra-Olcese, Carlos (2025)
Most studies on media education, literacy and competence focus on basic education and teacher training; in this context, university training for communicators has not received the attention we believe it should have. Therefore, this article presents the results of a systematic exploratory review, following the PRISMA ScR model, of 55 articles published in five scientific reference databases that present empirical studies on media education in university communication courses. The results show that, since 2019, there has been an increase in interest in this subject, that the largest amount of scientific work has been published in English, that nearly half of it presents a theoretical framework on topics related to media education, that quantitative methodologies prevail in the design of studies with the survey as the main tool. Finally, based on the analysis of the objects of study of the reviewed literature, a proposal of eight areas of interest is organized.